Uniformité et efficacité des garanties en matière de libertés publiques - Chevrette, François; Marx, Herbert (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
An entrenched Bill of Rights, it is maintained, would be of benefit not only to individuals and groups but also to provincial governments generally, because the same standards would apply at the federal as well as the provincial level. Such a Bill should include certain effective protections lacking in the present Canadian Bill of Rights. The protection of civil liberties by way of the division of powers has favoured the enhancement of federal power and has worked to the disadvantage of the provinces. What is proscribed at the provincial level is permitted at the federal level. In effect, although the provincial persecution and prosecution of Communists and Jehovah's Witnesses are well known, particularly because of their appearances before the courts, similar legislative and administrative policies on the part of the federal Government and Parliament have not surfaced as clearly in the Canadian constitutional process or history. This is also true as concerns the treatment of Asiatics. The formulation of the safeguards to be included in a Bill of Rights raises the question as to their scope and application. The present Canadian Bill of Rights has given rise to the situation where the act of an official, such as a police officer, is not subject to the provisions of the Bill whereas the legislative enactment that authorizes the act is so subject. An efficient Bill of Rights would control such acts as well as laws. Lastly, it is suggested that there is a general consensus in Canada as to the essential contents of a Bill of Rights. In dealing with emergency situations, the federal Government should have the burden of proving that an emergency exists and that restrictions imposed on specific civil liberties are required. At present the person contesting the invocation of the War Measures Act or other emergency legislation has the almost impossible task of proving that an emergency does not in fact exist.